Correlations among quality of life, spinal mobility, and disease activity in early-treated axial spondyloarthritis: a single-center cross-sectional study - Tinh Khampaen; Thanuchporn Kafaksom; Nichapa Dechapaphapitak; Nattakirana Tongdee; Parawee Chevaisrakul (BMC Rheumatology)
Abstract Background Axial spondyloarthritis (axSpA) significantly impacts patients’ lives. The ASAS-OMERACT guideline was formulated for the multidimensional evaluation of axSpA patients, employing a specific set of tools. Given the pivotal role of patient perception, comprehensive correlation among these tools, especially concerning quality of life, may provide a clinically relevant perspective and enhance treatment efficacy in the early stages of the disease. This study aims to investigate the correlation among disease activity, functional ability, and quality of life in early-treated axSpA patients. In addition, the association between high disease activity and clinical characteristics was explored. Methods This cross-sectional study was conducted in a tertiary hospital in Thailand. Patients diagnosed with axSpA according to ASAS classification criteria and receiving treatment from rheumatologists within three years of onset of symptoms were included. Clinical and laboratory data were retrieved from a hospital database. Disease activity was assessed using the Ankylosing Spondylitis Disease Activity Score with ESR or CRP (ASDAS-ESR/CRP) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Spinal mobility was measured using the Bath Ankylosing Spondylitis Metrology Index (BASMI), while quality of life and function were evaluated using the ASAS Health Index (ASAS-HI) and Bath Ankylosing Spondylitis Functional Index (BASFI), respectively. The correlation between these measurements was analyzed using the Pearson correlation coefficient (r). Additionally, factors associated with high disease activity (ASDAS/CRP > 2.1) were explored using multivariate regression analysis. Results Sixty-six patients (41 males; mean age 49.3 ± 13.3 years) were enrolled between April to December 2022. Disease activity (ASDAS-CRP) was significantly inversely correlated with spinal mobility (BASMI), function (BASFI), and quality of life (ASAS-HI). High disease activity was associated with obesity (BMI ≥ 30 kg/m^2) and a longer duration of symptoms before treatment (≥ 2 years). Conclusion In early-treated axSpA patients, ASDAS-CRP showed significant correlations with functional ability, quality of life, and spinal mobility. High disease activity was associated with obesity and a longer pre-treatment symptom duration in our study. Early treatment may enhance patients’ function, mobility, and quality of life, with weight reduction being possibly beneficial for obese axSpA patients. Clinical trial number Not applicable.